Determination of Phenolics and Flavonoids of Some Useful Medicinal Plants and Bioassay-Guided Fractionation Substances of Sclerocarya birrea (A. Rich) Hochst Stem (Bark) Extract and Their Efficacy Against Salmonella typhi - Abdallah, Muhammad Salihu; Mustafa, Muskhazli; Nallappan, Meenakshii A/P.; Choi, Sangho; Paik, Jin-Hyub; Rusea, Go (Frontiers in Chemistry, 2021)
Gallic acid and catechin are the most abundant phenolic and flavonoid contents found in all plant extracts. The contents and the bioassay-guided fractionating substances of the Sclerocarya birrea (A. Rich) Hochst (Anacardiaceae) fraction played vital roles. The goals of the study were to determine the contents of some useful medicinal plants and the bioassay-guided fractionation substances of S. birrea fraction compounds capable of acting against Salmonella isolate using LC-MS/LC-HRMS (Dionex ultimate 3000 RS UPLC with Thermo Scientific Q Exactive Orbitrap Hybrid Tandem Mass Spectrometer). The Folin–Ciocalteu reagent procedure and flavonoid content determination were conducted spectrophotometrically. Bioassay-guided fractionation, chronological partitioning, and screening of the antibacterial action against Salmonella typhi were performed. The ethyl acetate fraction extracts of S. birrea stem (bark) extract were analyzed using LC-MS/LC-HRMS. The gallic acid content increased tremendously in Vachellia nilotica (L.) P.J.H. Hurter and Mabb (Fabaceae) pod extracts with curve fitting (R2 = 0.9958). Catechin content increase was significantly increased in S. birrea stem (bark) extracts followed by that of V. nilotica pod extracts with curve fitting (R2 = 0.9993); they were all significantly different in the Guiera senegalensis J.F. Gmel. and the Leptadenia lanceolata (Poir.) Goyder leaves extracts at p value <0.0001. Subsequently, 10 mg/ml of S. birrea stem (bark) ethyl acetate fraction extract was the MIC, where no MBC was recorded and susceptible to the positive control with the highest inhibition zone, followed by the ethyl acetate fraction extract at 10 mg/ml (9.7 ± 0.0) at Turkey’s p < 0.0001. Vidarabine is one of the novel compounds, specifically having antimicrobial actions, found in the S. birrea stem (bark). Reasonable amounts of phenolic and flavonoid contents determined the actions of the individual plant extract.